Insights into Eukaryotic Translation Initiation from Mass Spectrometry of Macromolecular Protein Assemblies. Issue 2 (29th January 2016) - Schmidt, Carla; Beilsten-Edmands, Victoria; Robinson, Carol V.
Abstract: Translation initiation in eukaryotes requires the interplay of at least 10 initiation factors that interact at the different steps of this phase of gene expression. The interactions of initiation factors and related proteins are in general controlled by phosphorylation, which serves as a regulatory switch to turn protein translation on or off. The structures of initiation factors and a complete description of their post-translational modification (PTM) status are therefore required in order to fully understand these processes. In recent years, mass spectrometry has contributed considerably to provide this information and nowadays is proving to be indispensable when studying dynamic heterogeneous protein complexes such as the eukaryotic initiation factors. Herein, we highlight mass spectrometric approaches commonly applied to identify interacting subunits and their PTMs and the structural techniques that allow the architecture of protein complexes to be assessed. We present recent structural investigations of initiation factors and their interactions with other factors and with ribosomes and we assess the models generated. These models allow us to locate PTMs within initiation factor complexes and to highlight possible roles for phosphorylation sites in regulating interaction interfaces. Graphical Abstract: Highlights: Translation initiation is coordinated by several initiation factors. Phosphorylation is important for the regulation of initiation factors. Mass spectrometry can be used to study structures and phosphorylation of initiation factors. Ribosomes and initiation factors are ideal targets of many mass spectrometry studies.